Clinical Signs for Differential Diagnosis of Eyelid Tumours - Kopecky, Adam; Rokohl, Alexander Christopher; Gaca, Piotr Jakub; Matos, Philomena A Wawer; Nemcansky, Jan; Heindl, Ludwig M (Klinische Monatsblatter fur Augenheilkunde, 2023)
This article aims to present the differential diagnostics of benign and malignant eyelid tumours. The most common malignant eyelid tumour is basal cell carcinoma, followed by squamous cell carcinoma. The common signs of malignity are loss of lashes, ulceration, and infiltration of the lesion. Often the clinical appearance is various and therefore only a histological analysis gives the proper diagnosis. For most tumours, surgical resection is the gold standard of therapy. The reconstruction of the defects should be performed by an experienced oculoplastic surgeon. In malignant tumours that require large safety margins, the defect can be easily very large, and the reconstruction must then be performed with advanced ophthalmic plastic reconstruction techniques.
Keywords: nádory očního víčka; nádory kůže; bazocelulární karcinom; Eyelid Neoplasms; Humans; diferenciální diagnóza; zákroky plastické chirurgie; Diagnosis, Differential; Skin Neoplasms; lidé; Carcinoma, Basal Cell; Plastic Surgery Procedures